Design of Flexible Structural System for Building Customization - Diego Lozano; Ángel Martín; Miguel A. Serrano; Carlos López-Colina (Advances in Civil Engineering)
The main aim of this research work is to design a structural system for building customization, through simple industrialized components. The system is able to adapt to different orthogonal geometries and presents the necessary flexibility to allow modifications over the structure of the building throughout its life. The so-named “flexible structural system” (FSS) is characterized by using only small industrialized components, handled by one person, which exhibit an easy and simple assembly. The new system proposes the use of just two different pieces named basic units (BUi) with only two possible thicknesses for any of them. The system is composed of only 5 different pieces. The generating process of the structural system is based on different combinations of the basic units (BUi) to obtain resistant members (RMn). These resistant members allow to build structural frames (F), and finally, the addition of structural frames allows to generate diaphanous volumes (DV) and obtain the desired structure for the building. The limit of structural length is set at 4.8 meters. Finally, an example is shown where a structure for a diaphanous volume is obtained, using the referred industrialized elements. This shows that the system is systematic and easy to understand by users. We want the users themselves to design and build their own home as well as make the necessary modifications throughout the useful life of the building. This is the final objective.